ECMO as a bridge to decision: Recovery, VAD, or heart transplantation?. (6th May 2015) - Rousse, N.; Juthier, F.; Pinçon, C.; Hysi, I.; Banfi, C.; Robin, E.; Fayad, G.; Jegou, B.; Prat, A.; Vincentelli, A.
Abstract: Background: Our 8-year experience with ECMO support as a bridge to decision was reviewed. Methods: A cohort of 124 consecutive patients received ECMO for refractory cardiogenic shock in our institution. Twenty-six of these were out of hospital cardiac arrests and were excluded from this analysis. The median age was 43 years, in the range of 11 to 73 years. Results: The median duration of ECMO support was 4.5 days. Mortality while supported by ECMO was 50% with a median support time of 2 days. Weaning from ECMO was achieved for 49 patients with the following outcomes: cardiac recovery (60%), heart transplantation (26%), and VAD implantation (14%). Median duration of support before weaning was 8 days. Hospital survival was 83%, 61.5% and 71% for cardiac recovery, heart transplantation and VAD implantation, respectively. ECMO weaning was significantly improved in all patients who had normalized their renal function, and when duration of support > 6 days (HR: 4.255 [1.255–14.493], p = 0.02 and HR: 2.164 [1.152–4.082], p = 0.02, respectively). A creatinine level > 14 mg/l the day of weaning was a significant predictor of death (HR: 5.807 [1.089–30.953]; p = 0.04). Median follow up was 2.4 years; one-year survival rate was 78%, 51% and 75% for cardiac recovery, heart transplantation and VAD implantation, respectively. Conclusion: With at least 6 days of support, ECMO allowed a better patient selection for myocardial recovery, VAD implantation or heart transplantation. Whether VAD implantation or heart transplant in those patients is a better indication remains to be evaluated.